{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

ia2sp10h4s

# The third difficulty is proving the sequence actually

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: The third difficulty is proving the sequence actually converges to the assumed limit. The second and third difficulty are frequently interchangeable. We just overcame the first difficulty; if the sequence converges to anything it has to be to a . Back to the proof. The sequence { a n } is a Cauchy sequence, thus is bounded. (recall that Cauchy sequences are bounded!). In other words, there is some real number C > 0 such that k a n k 1 ≤ C for n = 1 , 2 , 3 ... . For every K ∈ N we have K X k =1 | a nk | ≤ ∞ X k =1 | a nk | = k a n k 1 ≤ C for n = 1 , 2 , 3 ,... . Since (it being a finite sum!) lim n →∞ K X k =1 | a nk | = K X k =1 | lim n →∞ a nk | = K X k =1 | a k | we see that K X k =1 | a k | ≤ C for all K , hence also k a k 1 = ∞ X k =1 | a k | ≤ C, proving a ∈ ‘ 1 . Finally, we need to show that k a n- a k 1 → 0 as n → ∞ . The problem her is to control well the tails of the sequences. Let ² > 0 be given. Because a ∈ ‘ 1 , there is K such that ∞ X k = K +1 | a k | < ² 2 . By the Cauchy condition, there is N such that k a n- a m k 1 < ²/ 2 whenever n,m ≥ N . Thus, for every p ≥ 1, n,m ≥ N , K + p X k = K +1 | a nk- a mk | ≤ k a n- a m k 1 < ² 2 . Keeping p fixed for a moment we let m → ∞ (the sum being finite, the limit can be interchanged with the sum) to conclude that K + p X k = K +1 | a nk- a k | < ² 2 for all p ∈ N , n ∈ N , n ≥ N . This being true for all p ≥ 1 it is also true for the limit as p → ∞ ; in other words, ∞ X k = K +1 | a nk- a k | < ² 2 if n ≥ N . Now (again because the sum is finite) lim n →∞ K X k =1 | a nk- a k | = 0 , thus there is N 1 such that K X k =1 | a nk- a k | < ² 2 if n ≥ N 1 . Let n ≥ max( N,N 1 ). Then k a n- a k 1 = ∞ X k =1 | a nk- a k | = K X k =1 | a nk- a k | + ∞ X k = K +1 | a nk- a k | < ² 2 + ² 2 = e proving that { a n } converges to a in ‘ 1 . NOTES: 1. If you got only 5 points for this exercise it is because I assumed that everybody would have no difficulty proving everything but the completeness, thus I emphasized that part of the problem. A 5 means that, in my opinion, your proof of completeness has profound flaws. But see also Note 3. 2. Several of you used (essentially) the following result without justification: If lim n →∞ a nk = a k , then (1) ∞ X k =1 | a k | = lim n →∞ ∞ X k =1 | a nk | ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 4

The third difficulty is proving the sequence actually...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online